Розробка рекомендаційної системи електронної комерції з продажу книжок - Синьова, В. О. (ХНУРЕ, 2024)
The report discusses the stages of designing and developing a recommendation system for e-commerce selling books, implementing a business function that allows recommending users books with the highest average rating among registered users, and books similar to the chosen one, using TF-IDF vectorization, cosine similarity, and Data Mining methods.
Keywords: рекомендаційна система; електронна комерція; продаж книжок; книжковий інтернет-магазин